2017
DOI: 10.1002/cssc.201700667
|View full text |Cite
|
Sign up to set email alerts
|

Intensified Biobutanol Recovery by using Zeolites with Complementary Selectivity

Abstract: A vapor-phase adsorptive recovery process is proposed as an alternative way to isolate biobutanol from acetone-butanol-ethanol (ABE) fermentation media, offering several advantages compared to liquid phase separation. The effect of water, which is still present in large quantities in the vapor phase, on the adsorption of the organics could be minimized by using hydrophobic zeolites. Shape-selective all-silica zeolites CHA and LTA were prepared and evaluated with single-component isotherms and breakthrough expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 70 publications
5
48
0
Order By: Relevance
“…It has been observed that the hydronium ions strongly affect adsorption properties in the micropore confines . On a macroscopic level, zeolites with very low concentrations of BAS display stronger adsorption of less polar organic substrates and are regarded as hydrophobic;– zeolites with high concentrations of BAS have higher affinity to water and are considered to be hydrophilic . However, it is challenging to link this macroscopic description of zeolites as hydrophobic or hydrophilic with their properties on an atomistic and molecular level.…”
Section: Figurementioning
confidence: 99%
“…It has been observed that the hydronium ions strongly affect adsorption properties in the micropore confines . On a macroscopic level, zeolites with very low concentrations of BAS display stronger adsorption of less polar organic substrates and are regarded as hydrophobic;– zeolites with high concentrations of BAS have higher affinity to water and are considered to be hydrophilic . However, it is challenging to link this macroscopic description of zeolites as hydrophobic or hydrophilic with their properties on an atomistic and molecular level.…”
Section: Figurementioning
confidence: 99%
“…Our defect‐free, hydrophobic MFI crystals produced in fluoride medium displays very high adsorption capacity of 1‐butanol (0.13 g g −1 zeolite) from a water solution, equal to the equilibrium adsorption ability estimated by Monte Carlo simulations . The 100 nm CHA crystal shows very high 1‐butanol adsorption (0.18 g g −1 zeolite) from aqueous solution, which is two times higher than the reported adsorption of micrometer sized Si‐CHA crystals from vapor‐phase . Furthermore, the MFI crystals are obtained in very high yield (98 %), while the yield of nanosheets is around 10 % …”
Section: Figurementioning
confidence: 63%
“…ITQ-29 has been proven to be the most hydrophobic of the LTA zeolites, based on the isosteric heat of CO 2 adsorption, making this zeolite a suitable adsorbent for natural gas upgrading, due to its high regenerability and adsorption capacity of CO 2 over CH 4 [ 25 , 26 ]. Also, ITQ-29 has been studied for the isolation of biobutanol from an aqueous acetone–butanol–ethanol (ABE) fermentation media [ 27 ], but in this case, using ITQ-29 zeolite in powder or as an extrudate. It was possible to reach a butanol purity of >99.5%, at a recovery of >99% by combining columns of hydrophobic ITQ-29 zeolite and the polar SAPO-34 (silicoaluminophosphate of CHA structure).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that all silica ITQ-29 adsorbed 1 wt.% water at 20 mbar and 298 K compared with 26 wt.% in the case of CaA (same LTA structure with Si/Al ratio of 1 and Ca as charge compensating cations) [ 24 ]. More recently, the water adsorption was quantified in 4 wt.% measured at 85% humidity and 313 K, being significantly lower than the capacity of other pure silica zeolite (Chabazite) that adsorbed 8 wt.% under the same conditions [ 27 ]. The hydrophobicity of the ITQ-29 zeolite is compared in the present work with that of a very well-known and reported hydrophobic zeolite, such as Silicalite-1 (MFI structure).…”
Section: Introductionmentioning
confidence: 99%